Prognostic value of triploid zygotes on intracytoplasmic sperm injection outcomes - Figueira, Rita C. S. (Springer US, 2011)
PURPOSE: To evaluate the prognostic significance of triploidy incidence on the outcomes of embryos derived from normally fertilized oocytes from the same cohort. METHODS: This study included 1500 ICSI cycles. Logistic regression models were used to study the influence of abnormal fertilization on the development and clinical outcomes of embryos derived from normally fertilized oocytes from the same cohort RESULTS: We observed a negative influence of the percentages of triploid zygotes on fertilization (75.2% and 56.8%, P < 0.0001), high-quality embryos (58.9% and 48.2%, P = 0.0001), pregnancy (34.1% and 28.2%, P = 0.0540) and implantation rates (20.0% and 13.3%, P = 0.0012). When the 3PN zygote rate was >25%, the percentages of normal fertilization, high-quality embryos and implantation rates were significantly lower than in the control group. CONCLUSIONS: We observed an approximately 50% lower risk of pregnancy and a 3.5-fold higher risk of miscarriage in cycles with a 3PN incidence of >25%.